Edukasi Kesehatan sebagai Upaya Pencegahan Infeksi Cacing pada Siswa-Siswi di SDN Girikulon, Kecamatan Secang, Kabupaten Magelang - Kartika, Intan Amalia; Ayu, Sukma; Imani, Ikhsan Sabil; Chairunisa, Allaya Putri; Putra, Yehizkia Tectona; Nugraha, Joko Tri (Universitas Pahlawan Tuanku Tambusai, 2026)
Soil-transmitted helminth infections remain a major public health concern among elementary school children in Indonesia, with a prevalence rate of 31.8%. This community service program aimed to improve students’ knowledge of helminth infection prevention through structured health education. The activity targeted 17 fourth-grade students at SDN Girikulon and used an interactive discussion approach supported by PowerPoint presentations and animated videos. The program consisted of three stages: preparation, including coordination and development of learning materials; implementation, consisting of pre-test, material delivery, post-test, and discussion; and evaluation through comparison of test results. The findings showed a significant increase in knowledge, with average scores rising from 46.5 to 94.1 after the intervention. These results indicate that interactive health education effectively enhances students’ understanding of helminth prevention. For sustainability, collaboration with local health centers or the Health Office is recommended to expand program coverage and ensure equitable distribution of deworming medication to all students.